Histologic and Immunohistochemical Evaluation of Infiltrating Inflammatory Cells in Kawasaki Disease Arteritis Lesions. Issue 1 (January 2021) - Kobayashi, Mikiko; Matsumoto, Yuki; Ohya, Maki; Harada, Kenichi; Kanno, Hiroyuki
Abstract : Kawasaki disease (KD) is a systemic vasculitis of unknown etiology which predominantly affects medium- and small-sized muscular arteries. Histopathologic studies of KD vasculitis lesions have demonstrated characteristic T cell infiltration and an abundance of CD8 + T cells; however, the contribution of cytotoxic lymphocytes to KD vasculitis lesions has not been identified. Here, we histopathologically and immunohistochemically examined infiltrating inflammatory cells, particularly cytotoxic protein-positive cells, such as granzyme B + cells and TIA-1 + cells, in KD vasculitis lesions. Three autopsy specimens with acute-phase KD were observed and contained 24 vasculitis lesions affecting medium-sized muscular arteries, excluding pulmonary arteries. Infiltrating neutrophils in vasculitis lesions were evaluated by hematoxylin and eosin staining, and monocytes/macrophages and lymphocytes were evaluated by immunohistochemistry. The predominant cells were CD163 + monocytes/macrophages and CD3 + T cells. CD8 + T cells, granzyme B + cells, and TIA-1 + cells were also observed, but CD56 + natural killer cells were rare. To the best of our knowledge, the current study is the first histopathologic report confirming the infiltration of inflammatory cells with cytotoxic proteins in vasculitis lesions in patients with KD. Cytotoxic T cells may play a role in the development of vasculitis lesions in KD patients.